DAMPAK POSITIF BERORGANISASI DAN BUDAYA ORGANISASI BAGI MAHASISW DAN PEKERJA GENERASI Z - A.putri Andini; Natasyah Natasyah; Haedar Haedar (Universitas Slamet Riyadi, 2024)
This research aims to determine the positive impact of organizations and organizational culture on generation z students and workers. The position of the organization is quite important in aspects of life both in industry, government, social organizations, society and others. Organizations as part of the branch of social science have a fairly large role in human life. Organizational culture refers to shared assumptions. Organizations can occur if there is a group of people working together to achieve the same goal.